Transesterification of Jatropha Curcas L. oil to biodiesel using Nd2O2 and Bi2O2 -supported catalysts - Md Fahmy, Rabiah Nizah (2015)
Biodiesel is gaining more attention since it is a renewable source of energy that can be an alternative for petroleum based diesel fuels. Other than being renewable, it is also biodegradable and non-toxic. Biodiesel is even more preferable since it can be produced easily via transesterification reaction. With various resources that can be used to produce biodiesel, Jatropha Curcas oil (JCO) is one of the feasible source since it is a non-edible oil, hence no competition over food resources. One of the major drawback of JCO is that it contains high amount of free fatty acids (FFA). In this study, catalyst with different catalyst (Nd2O3 and Bi2O3) on La2O3 support were compared. Bi2O3 catalyst shows higher catalytic activity at lower reaction conditions, hence is used for further study. Different loading of Bi2O3 (1,3,5,7 wt.%) using La2O3 as a support were prepared using wet impregnation method for simultaneous esterification and transesterification of JCO and its potential as heterogeneous catalyst was assessed. The catalysts were characterized by using Xray Diffractometer (XRD), Brunauer-Emmett-Teller (BET) surface area, Scanning Electron Microscopy (SEM) and Temperature Programmed Desorption (TPD) of CO2 and NH3. These catalysts were then used for transesterification reaction under different reaction conditions (methanol to oil molar ratio, amount of catalyst,reaction temperature and reaction time) to investigate the catalytic activities of the catalysts. Under optimum transesterification condition at 150°C with catalyst amount of 2 wt.%, methanol/oil molar ratio of 15:1 and reaction time of 4 h,5BiLa catalyst gave fatty acid methyl ester (FAME) conversion of 93%. The catalytic activities were found depending on the acidity, basicity and the surface area of the catalyst used. Several tests were conducted to study the physicochemical properties of the product such as pour point, flash point,kinematic viscosity, sulphur content and cloud point of biodiesel produced. Based on the results, the synthesized biodiesel is comparable with conventional diesel in the market since it meets the international standards of biodiesel which are American Standard for testing Materials (ASTM), Europian Standard (EN) and Malaysian Standard (MS) for diesel fuel specifications.